Potensi Integrasi Pembelajaran Biologi dengan Pembelajaran Quran-Hadis - Ahmad Naharuddin Ramadhan; Siti Irene Astuti Dwiningrum; Bustami Subhan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The Potential of Integration between Biology Learning and Quran-Hadith LearningBecause the secular Western perspective is influential until now, the dichotomization of religion and science is very strong. Religion and science are often seen as conflicting, have a different realm of explanation, and cannot be reconciled. This view also has an impact on science learning and Islamic religious education in madrasas or religious schools. If the appreciation of the syar'iyyah verses can be synergized with knowledge of the kauniyyah verses, the benefits will be more significant and make the learning process more meaningful. This study explores the potential for integration or the common ground between discussions in Biological science with studies of the Qur’an and Hadith. The novelty of this study is to provide a deeper portion highlighting the traditions of the Prophet. This study also explores the content of Qur’anic verses or hadiths relatively rarely raised in previous studies. It shows the breadth of the potential for religion-science integration both from the Qur’anic verses and the Prophet Muhammad's traditions with the theme of faith, jurisprudence, and morals. This research was conducted using a qualitative approach with library research techniques. The results of this study indicate that learning biology with learning the Qur’an and Hadith can be integrated. The integration model can be classified into two, namely: (1) strengthening the study of Qur’anic verses and the Prophet's traditions, and (2) enriching the teaching of a Biology material by studying the Qur’anic verses or relevant traditions